Feedback on Reading and Writing: Exploring Students’ Experience and Preferences - Mardiah, Radiatan; Melati; Ulfiati, Lilik; Safitri, Nyimas Triyana (UNIB Press, 2025)
Feedback plays a crucial role in achieving learning objectives. This study explores students’ experience and preferences in feedback provision and its implications on reading and writing instruction. This study applied a qualitative research design with a case study method. The participants were ten fifth-semester students of the 2023/2024 academic year of the English education study program at a public university in Jambi, Indonesia. A focus group discussion with the students was used to explore their experiences and preferences, supported by the data from the learning management system (LMS) of the university. Furthermore, the data were analysed using thematic analysis. The findings revealed that feedback was provided by lecturers and peers, both in online and offline modes. The peers provided more informal feedback, and lecturers provided more detailed and natural feedback on the students’ reading and writing exercises. While students appreciated peer feedback, they also felt uncertain when they received feedback from peers. In addition, the students preferred face-to-face direct constructive feedback, which can help them increase self-awareness and understand more details. However, being loaded with other teaching tasks and academic activities on campus, lecturers could not fully meet this particular preference. Thus, as the pedagogical implication, multimodal feedback which is personalized to enable students to feed forward in their own individual learning journeys should be used.